Autologous Platelet- and Extracellular Vesicle-Rich Plasma Is an Effective Treatment Modality for Chronic Postoperative Temporal Bone Cavity Inflammation: Randomized Controlled Clinical Trial - Vozel, Domen; Božič, Darja; Jeran, Marko; Jan, Zala; Pajnič, Manca; Pađen, Ljubiša; Steiner, Nejc; Kralj-Iglič, Veronika; Battelino, Saba (Frontiers in Bioengineering and Biotechnology, 2021)
Purpose: To determine the efficacy of autologous platelet- and extracellular vesicle-rich plasma (PVRP) to treat chronic postoperative temporal bone cavity inflammation (CPTBCI) after exhausted surgical and standard conservative therapy. Materials and methods: Patients were randomly allocated to treatment with PVRP (PVRP group) or standard conservative methods (control group) in a setting of four once-monthly check-ups and subsequent follow-up. The treatment outcome was measured with COMQ-12 (chronic otitis media questionnaire-12), CPTBCI focus surface area, and CPTBCI symptom-free time after the fourth check-up. Results: 11 patients from each group completed the trial; 95% of patients suffered from chronically discharging mastoid cavity (the type of CPTBCI). Within four check-ups, the COMQ-12 score decreased statistically significantly in the PVRP group (p<0.001) but not in the control group (p=0.339). CPTBCI foci surface area decreased statistically significantly between the first and second check-ups (p<0.0005), but not between other check-ups (p>0.05) in the PVRP group. No statistically significant differences in CPTBCI foci surface area were detected between check-ups in the control group (p=0.152). Nine patients from the PVRP and three from the control group were CPTBCI symptom-free at the fourth check-up. The median symptom-free time was 9.2 months (95% CI [7.4, 11.9]) in the PVRP group. Cumulatively 49% of patients in the PVRP group remained CPTBCI symptom-free for 12.7 months after the fourth check-up. Conclusion: Autologous PVRP represents a novel additional and successful treatment modality for chronically discharging radical mastoid cavity when the surgical and standard conservative treatment methods have been exhausted. Trial number: NCT04281901 (https://clinicaltrials.gov).